2017
DOI: 10.1080/1744666x.2017.1392855
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells in the pathogenesis of periodontitis: potential novel treatment strategies

Abstract: Introduction Periodontal diseases are polymicrobial inflammatory disorders of the tissue, ligament, and bone structures supporting teeth. Periodontitis (inflammation with corresponding loss of attachment) affects 40–50% of adults. Recently, members of the Triggering Receptor on Myeloid Cell (TREM) family have been studied to determine their relationship to these diseases. Areas covered TREM-1 is a receptor expressed on the surface of PMNs, monocytes, macrophages, dendritic cells, vascular smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…Romandini et al [ 54 ] concluded that periodontitis influences WBC count by an increase in systemic inflammation, and Arai et al [ 55 ] concluded that WBC is independently associated with CKD progression. These two articles that studied WBC showed high levels in patients with periodontitis, suggesting a systemic inflammation caused by periodontitis [ 37 , 46 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romandini et al [ 54 ] concluded that periodontitis influences WBC count by an increase in systemic inflammation, and Arai et al [ 55 ] concluded that WBC is independently associated with CKD progression. These two articles that studied WBC showed high levels in patients with periodontitis, suggesting a systemic inflammation caused by periodontitis [ 37 , 46 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Host modulation therapies (Bartold and Van Dyke, 2017 ; Hajishengallis et al, 2020 ) combining anti-inflammatory and antioxidant agents have shown promising effects to treat PD in clinical trials (Sulijaya et al, 2019 ). Other biologics used as novel therapeutic strategies involve molecules able to trigger myeloid cell receptors (Rudick et al, 2017 ) since these cells are known players in pathogenic inflammation (Peddis et al, 2019 ). The novel anti-inflammatory drug tetramethylpyrazine has been recently found to reduce inflammation levels as well as LPS-mediated apoptosis in human periodontal ligament cells by a mechanism involving the downregulation of the small non-coding RNA miR-302b (Duan et al, 2020 ).…”
Section: Medical Aspects Of Periodontal Inflammationmentioning
confidence: 99%
“…Periodontitis is a biofilm-driven chronic inflammatory disease during which a dysbiotic periodontal microbiota induces adverse immune responses that further lead to the destruction of tooth-supporting tissues and ultimately tooth loss [19][20][21] . Several studies have investigated TREM-1 and PGLYRP1 in the context of periodontal disease and recently TREM-1 has been suggested as a candidate marker for new treatment strategies against periodontal diseases 22,23 . Elevated TREM-1 levels were observed in saliva, serum and gingival crevicular fluids (GCF) in patients with periodontitis, and TREM-1 serum and saliva levels correlated positively [24][25][26][27] .…”
mentioning
confidence: 99%